Core-shell granular activated carbon and its adsorption of trypan blue. (1st January 2020) - Cai, Zhenghan; Deng, Xiuchun; Wang, Qiong; Lai, Jianjun; Xie, Hailiang; Chen, Yandan; Huang, Biao; Lin, Guanfeng
Abstract: Granular activated carbon (GAC) and powder activated carbon (PAC) have many disadvantages that limit their application as adsorbent. Thus, a novel core-shell granular activated carbon (WS@AC) was designed and can be used to adsorb trypan blue. WS@AC was prepared using PAC as the core and wood powder and silica sol as the shell. The preparation was achieved by a facile method. The morphology and pore structure of the developed WS@AC were observed by scanning electron microscopy, and its N2 adsorption-desorption isotherm was determined. WS@AC was obtained under the optimal conditions where the wood powder/core ratio was 0.40, silica sol/wood powder ratio was 2.0, and heat treatment was at 250 °C for 1.5 h. The results showed that the WS@AC had a specific surface area of 1127.8 m 2 /g and the abrasive resistance of 99.24%. The adsorption of trypan blue experiment showed that PAC and PAC in WS@AC (PAC-WS@AC) reached the highest adsorption capacity of 115.6 mg/g and 113.2 mg/g, respectively, which further showed that the adsorption capacity of PAC-WS@AC was fully utilized. The results also showed that the WS@AC was able to overcome the disadvantage of GAC where the superficial carbon could block the adsorption of trypan blue from the core carbon, thus improving the efficiency of adsorption. This work provides a foundation for the production and development of GAC, as well as other particle adsorbents or catalysts. Graphical abstract: Image 104 Highlights: High performance core-shell structure granular activated carbon was prepared. WS@AC possesses both the strength of GAC and the fast adsorption performance of PAC. The adsorption capacity of PAC in WS@AC would be fully utilized.